5 - Transition énergétique et mouvements sociaux à Abidjan : une analyse dialectique des perceptions de la population abidjanaise face à la politique étatique de distribution d’ampoules à basse consommation - Kabran Aristide DJANE (African Sociological Review, 2019)
The question of ecological transition has fundamentally restructured the process of producing mass consumption energies in various developed countries; nevertheless, it remains a question not yet deepened both in the political sphere and in the scientific structures, even if impulses begin to manifest themselves. An example of this is the Cheikh Anta Diop University Symposium on the “Smart City” in November 2017, which allowed us to reflect on the question of new approaches to energy consumption in African cities. Moreover, the Ivorian experience invites us to question the perceptions of the consumers of Abidjan and their attitudes towards the public policy of distribution of LED bulbs, said to low consumption. Indeed, during the year 2012 to 2014, the Ivorian government began with the support of the World Bank, and the electrification company, an operation to replace household light bulbs with LED bulbs. But against all odds, consumers have seen their consumption bill climb. This situation has developed a wave of popular protest among consumers. Our production aims to analyze, in the light of Alain Touraine’s theory of collective action, a dialectical and historicist approach, African social resistance and the dynamics of cognitive transformation allowing the appropriation of policies on the energy transition from the ground up. A mixed survey of 217 households in the city of Abidjan on this issue allowed us to grasp the analytical structuring of perceptions and the dynamics of collective attitudes towards the energy transition policy in Côte d’Ivoire.